MEMBANGUN KEMBALI “KESANTUNAN” BAHASA HUKUM DALAM PERUNDANGAN-UNDANGAN RI - Muhammad Abdullah (Faculty of Law, Universitas Diponegoro, 2013)
Abstract Register for law and legislation is realized in the specific style. There are characteristics of the various languages for law that include (1) straightforward, no elastic, (2) clear and unequivocal, (3) instructive in style, (4) less accommodating, and (5) specific and difficult to understand. The such characteristics make text using the language for law ambiguity. Looking at the above- phenomenon we realize that it is necessary to construct the language for law that is proper and accurate. Therefore, a new breakthrough and good will from the law practitioners are needed. Creating the register that is more communicative and responsef for the future is important to be realized Keywords: A language for law, legislation, communicative, effective. Abstrak Bahasa Indonesia dalam bidang hukum dan perundang-undangan memiliki gaya bahasa yang bersifat khusus. Adapun karakteristik ragam bahasa hukum adalah (1) bersifat lugas, tidak elastis, (2) jelas dan tegas, (3) bergaya bahasa instruktif, (4) kurang akomodatif, dan (5) bersifat khusus, susah dipahami pemabaca umum. Dengan performance bahasa hukum yang demikian itu, maka teks-teks bahasa hukum seringkali menimbulkan ambiguitas makna (multi tafsir) di kalangan masyarakat. Maka diperlukan sebuah terobosan baru dan good will dari praktisi hukum untuk memberikan ruang bagi terciptanya bahasa hukum yang lebih komunikatif dan efektif di masa depan. Kata kunci : bahasa hukum, bahasa perundang-undangan, komunikatif, efektif